2021
DOI: 10.3390/su131910928
|View full text |Cite
|
Sign up to set email alerts
|

Green Restaurants ASSessment (GRASS): A Tool for Evaluation and Classification of Restaurants Considering Sustainability Indicators

Abstract: Green restaurants are based on the implementation of environmental management and are closely related to quality management through a set of instruments and programs. This study aimed to build an instrument classification adopting cutoff points and classify restaurants using traffic light scores from the sustainability assessment checklist validated in Brazilian Portuguese for restaurants. The questionnaire classification validation was performed using a cross-sectional study conducted in a convenience sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…However, considering that during the production of meals both water and energy are essential factors for the operation of the service, the training of a school’s employees and the monitoring of the intended use of these resources is necessary. Instruments created to evaluate sustainability practices in food services, which include among their analysis categories the rational use of energy and water, are helpful tools in this regard [ 107 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, considering that during the production of meals both water and energy are essential factors for the operation of the service, the training of a school’s employees and the monitoring of the intended use of these resources is necessary. Instruments created to evaluate sustainability practices in food services, which include among their analysis categories the rational use of energy and water, are helpful tools in this regard [ 107 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, considering that during the production of meals both water and energy are essential factors for the operation of the service, the training of a school's employees and the monitoring of the intended use of these resources is necessary. Instruments created to evaluate sustainability practices in food services, which include among their analysis categories the rational use of energy and water, are helpful tools in this regard [107,108]. Environmental and health damage to the population generated by how the food system has been operated is already well established [109].…”
Section: Discussionmentioning
confidence: 99%
“…The sustainability of food preparation involves three principal considerations, including how the meal components are chosen and put together, the use of carbon-intensive foodstuffs, and how waste is managed [62]. Numerous studies have identified sustainable practices in food preparation, like purchasing renewable energy, using energy-efficient cooking routines, putting dishes on the menu that use less meat and more vegetables, preparing meals only after orders have been placed, planning purchases to avoid waste, nose-to-tail/root-to-leaf eating, reducing disposables, fermenting excess foodstuff, and composting food waste [2,6,7,62]. These practices usually contribute to environmental sustainability.…”
Section: Sustainable Preparationmentioning
confidence: 99%
“…20). Several studies have provided insight into the economic, social, and environmental dimensions of sustainability in the restaurant industry [4,5], with criteria developed to evaluate a restaurant's sustainability, such as restaurant and food service life cycle assessment [6], and Green Restaurants ASSessment (GRASS) [7]. A number of organisations have also launched accreditation schemes and certifications to distinguish sustainable restaurants, such as the Michelin Green Star [8],…”
Section: Introductionmentioning
confidence: 99%